A low-cost and advanced SiOx–C composite with hierarchical structure as an anode material for lithium-ion batteries1. Issue 20 (28th May 2015) - Wu, Wenjun; Shi, Jing; Liang, Yunhui; Liu, Fang; Peng, Yi; Yang, Huabin
<x xml:space="preserve">Abstract</x> By using low-cost methods, a SiOx–C composite with hierarchical structure was applied as a high performative anode material for lithium-ion batteries.